HOW GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE, AND CSR AWARDS IMPACT THE FINANCIAL SUCCESS OF ENERGY COMPANIES - Aulia Wahyu Nitasari; Sasongko Budisusetyo (Reviu Accounting, Business & Organizations, 2025)
Research Objective – To investigate the impact of green accounting, environmental performance, and CSR Awards on financial performance Research Method – Using secondary data with multiple linear regression analysis Research Findings – CSR Awards indeed have an impact on financial performance, as companies receiving CSR Awards have a positive image and are trusted by the public for successfully implementing corporate social responsibility programs Theoretical and Policy Implications – Importance of companies paying attention to environmental aspects as it will affect financial performance and implementing accounting Novelty of the Research – Importance of Green accounting and corporate concern